3, 4-Dihydroxyphenylacetaldehyde synthase and cuticle formation in insects. (June 2018) - Liao, Chenghong; Upadhyay, Archana; Liang, Jing; Han, Qian; Li, Jianyong
Abstract: Cuticle is the most important structure that protects mosquitoes and other insect species from adverse environmental conditions and infections of microorganism. The physiology and biochemistry of insect cuticle formation have been studied for many years and our understanding of cuticle formation and hardening has increased considerably. This is especially true for flexible cuticle. The recent discovery of a novel enzyme that catalyzes the production of 3, 4-dihydroxyphenylacetaldehyde (DOPAL) in insects provides intriguing insights concerning the flexible cuticle formation in insects. For convenience, the enzyme that catalyzes the production DOPAL froml -dopa is named DOPAL synthase. In this mini-review, we summarize the biochemical pathways of cuticle formation and hardening in general and discuss DOPAL synthase-mediated protein crosslinking in insect flexible cuticle in particular. Highlights: Insect cuticle formation was briefly described. Insect cuticular proteins were reviewed. Biochemical characteristics of DOPAL synthase were reviewed. The involvement of DOPAL synthase in flexible cuticle formation was proposed.